2022
DOI: 10.1177/02683555211061011
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of change in limb volume on functional mobility, health-related quality of life, social appearance anxiety, and depression in patients with lower extremity lymphedema

Abstract: Objectives This study aims to investigate the impact of change in limb volume on the levels of functional mobility, health-related quality of life, social appearance anxiety, and depression before and after complex decongestive physiotherapy in patients with lower extremity lymphedema. Method Twenty-seven patients with unilateral lower extremity lymphedema were included. The treatment period was 20 sessions. The outcome measures were the limb volume, the Timed Up and Go test, the Short Form-36, the Social Appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…[20][21][22][23][24] Similarly, in patients with lymphedema, limb volume reduction has demonstrated improvement in the mobility of patients with obesity. 25 This suggests the risk of VTE is higher in the elderly individuals with lymphedema and may also be observed in lipedema. Because limited mobility is common to lymphedema and lipedema and is more frequent in patients with obesity, this may potentiate the over-all combined risk of VTE.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23][24] Similarly, in patients with lymphedema, limb volume reduction has demonstrated improvement in the mobility of patients with obesity. 25 This suggests the risk of VTE is higher in the elderly individuals with lymphedema and may also be observed in lipedema. Because limited mobility is common to lymphedema and lipedema and is more frequent in patients with obesity, this may potentiate the over-all combined risk of VTE.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in patients with malignant tumors has led to the rise in patients with secondary limb lymphedema, which seriously affects mental health and quality of life. 20,23,24 The accompanying derangement in esthetics and functioning possibly leads to depression, anxiety, and a negative body image. 25 Secondary lower limb lymphedema is a common complication of cancer treatment, which frequently follows the radical resection of endometrial cancer, ovarian cancer, bladder cancer, and other malignant tumors, simple lymph node dissection, tumor radiotherapy, and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The calculation formula for the score of the Lymph-ICF-LL full scale and subscale is (the sum of the scores of the questions answered/the number of answered questions) × 10; hence, the score range of the full scale and each subscale is from 0 to 100. Five levels of lower limb lymphedema were identified using overall and subscale scores of Lymph-ICF-LL: no edema (score 0-4), mild edema (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), moderate edema (25-49), severe edema (50-95), and very severe edema (96-100). Research results have shown that Lymph-ICF-LL has good reliability and validity in both Chinese version 20 and other language versions.…”
Section: Lower Extremity Lymphedema Indexmentioning
confidence: 99%
“…If not intervened in time, the lesion site may permanently severe swelling, leading to disability, which will have a tremendous negative impact on the patient's physical and psychological state. 6,7 Currently, the treatment methods for lymphedema include conservative treatment, lesion tissue resection, liposuction, lymphaticovenular anastomosis (LVA), and lymph node transplantation. [8][9][10][11] With the progress of microsurgery equipment and technology, super microsurgery has been used to perform LVA in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…If not intervened in time, the lesion site may permanently severe swelling, leading to disability, which will have a tremendous negative impact on the patient’s physical and psychological state. 6,7…”
Section: Introductionmentioning
confidence: 99%